KESELARAN MANUSIA DAN ALAM DALAM PANTUN BATOBO (KAJIAN EKOKRITIK DAN SEMIOTIK) - Puspita, Alvi (Jurnal Ilmu Budaya, 2021)
This study examines Pantun Batobo, Kampar oral literature using ecocritical and semiotic theories. Pantun Batobo is a poem sung by batobo actors (mutual cooperation in farming) in the cultural areas of Kampar, Kuantan Singgigi, and Inderagiri. This pantun is intended as a remedy for fatigue because batobo actors work from morning to evening. This pantun can be classified into the cultural products of an agrarian society. To study the pantun, ecocritical and semiotic theories are used. Methods used interview techniques and literature while for data analysis used descriptive analysis methods. The results of this study are found the concept of harmony between humans and nature in the Pantun Batobo.